Nursing care in a patient with hysterectomy for cervical cancer - Corvera-Carhuapuma, Deny; Cabanillas-Chavez, María Teresa; Morales-García, Wilter C. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Cervical cancer continues to be the leading cause of death worldwide for many women, this type of cancer does not start suddenly, but has a previous evolution from precursor or precancerous lesions, the diagnosis is made in advanced stages of the disease, decreasing or canceling the chances of curative treatment. It is expected that by the year 2032 there will be 21.4 million new patients dealing with this disease in the world. Objective: To develop specialized and individualized comprehensive nursing care in patients with cervical cancer, based on scientific evidence recommendations and interventions. We present the assessment of a post-operative hysterectomy patient for cervical cancer where the nursing care process is applied. Methodology: A clinical case study, a 44-year-old patient was selected for convenience, applying the methodology of the nursing care process, the assessment was made through the 11 functional patterns of Marjory Gordon, the data were obtained from the clinical history, interview and physical examination of the patient. The main human responses are identified to analyze objective and subjective data, clinical judgments are made to implement care plans under the NANDA, NOC, NIC taxonomy. Results: 7 altered patterns were identified; considering as main diagnosis: acute pain and risk of complication; hemorrhage. Nursing care plans were implemented according to the Area model. A change score of +1 and +2 was obtained, which subsequently improved with nursing care. Conclusions: after the surgical procedure; According to the altered patterns, the nursing care process was carried out, observing improvement in the altered patterns, however, the patient remained hospitalized to continue with the specialized therapeutic plans, this implies that the gynecological-obstetric service must have professionals in nursing specialized in this area.